Optimizing electrode placement and information capacity for local field potentials in cortex - Willis, Jace A; Wright, Christopher E; Zhu, Ruoqian; Ruan, Yilan; Stallings, Joshua; Abrego, Amada M; Medani, Takfa; Moitra, Promit; Mosher, John C; Ramakrishnan, Arjun; Joshi, Anand Alan; Leahy, Richard M; et al. (bioRxiv, 2025)
Recent neurosurgery advancements include improved stereotactic targeting and increased electrode contacts. This study introduces a subject-specific, in silico modeling tool for optimizing electrode placement and maximizing coverage with a variety of devices. The basis for optimization is the inherent information patterns of field potentials derived from dipolar sources. The approach integrates subject-specific MRI data with finite element modeling (FEM) used to simulate the sensitivity of subdural and intracortical devices. Sensitivity maps, or lead fields, from these models enable the comparison of different electrode placements, contact sizes, contact configurations, and substrate properties, which are often overlooked factors. One tool is a genetic algorithm that optimizes electrode placement by maximizing information capacity. Another is a sparse sensor method, Sparse Electrode Placement for Input Optimization (SEPIO), that selects the best sensor subsets for accurate source classification. We demonstrate several use cases for clinicians, engineers, and researchers. Overall, these open-source tools offer a quantitative framework to juxtapose devices in one's neurosurgical armament or optimize device and contact placement. It may help users refine electrode coverage with low channel count devices and minimize invasive surgery burden. The study demonstrates that optimized electrode placement significantly improves the information capacity and signal quality of LFP recordings. The tools developed offer a valuable approach for refining neurosurgical techniques and enhancing the design of neural implants.